Age of first exposure to soccer heading: Associations with cognitive, clinical, and imaging outcomes in the Einstein Soccer Study - Charney, Molly F.; Ye, Kenny Q.; Fleysher, Roman; DeMessie, Bluyé; Stewart, Walter F.; Zimmerman, Molly E.; Kim, Mimi; Lipton, Richard B.; Lipton, Michael L. (Frontiers in Neurology, 2023)
Introduction The objective of this study is to assess the role of age at first exposure (AFE) to soccer heading as a predictor of known adverse associations of recent and longer-term heading with brain microstructure, cognitive, and behavioral features among adult amateur soccer players. Methods The sample included 276 active amateur soccer players (196 male and 81 female) aged 18–53 years old. AFE to soccer heading was treated as a binary variable, dichotomized at ≤ 10 years vs. >10 years old, based on a recently promulgated US Soccer policy, which bans heading for athletes ages 10 and under. Results We found that soccer players who began heading at age 10 or younger performed better on tests of working memory (p = 0.03) and verbal learning (p = 0.02), while accounting for duration of heading exposure, education, sex, and verbal intelligence. No difference in brain microstructure or behavioral measures was observed between the two exposure groups. Discussion The findings indicate that, among adult amateur soccer players, AFE to heading before age 10 compared to later start of heading, is not associated with adverse outcomes, and may be associated with better cognitive performance in young adulthood. Cumulative heading exposure across the lifespan, rather than early life exposure, may drive risk for adverse effects and should be the focus of future longitudinal studies to inform approaches to enhance player safety.